Insights to pseudocapacitive charge storage of binary metal-oxide nanobelts decorated activated carbon cloth for highly-flexible hybrid-supercapacitors. (October 2020) - Javed, Muhammad Sufyan; Khan, Abdul Jabbar; Asim, Sumreen; Shah, Syed Shoaib Ahmad; Najam, Tayyaba; Siyalg, Sajid Hussain; Tahir, Muhammad Faizan; Zhao, Zhijuan; Mai, Wenjie
Highlights: ZnCo2 O4 nanobelts are in-situ synthesized on flexible carbon cloth by cost-effective hydro-thermal method. The fabricated binder-free ZCO@CC electrode demonstrated hybrid charge-storage properties. Ex-situ XRD and XPS analysis are used to probe the electrochemical charge storage process of ZCO@CC. The flexible all-solid-state hybrid ZCO@CC||AC@CC SC exhibited excellent energy density of 79.48 Wh kg −1 at 894.24 W kg −1 . Abstract: Although cobalt/zinc-based bimetallic oxides are regarded as auspicious pseudocapacitive electrode materials owing to their high specific-capacitance and rich electrochemistry; however, relatively large capacitance fading during charge/discharge process and low energy-density hinder their real applications. In this work, we rationally designed a bimetallic oxide (ZnCo2 O4 ) nanobelt-decorated activated carbon-cloth composite (ZCO@CC) electrode by economical hydrothermal method for hybrid supercapacitors. The binder-free ZCO@CC electrode displays excellent electrochemical properties by attaining the high specific-capacitance of 1197.14 F g −1 (838 C g −1 ) at 2 A g −1 with good rate-capability of 75.18 % at 10 A g −1 . The hybrid nature of the stored charge is analyzed by manipulating power's law, which reveals that the diffusion-controlled and pseudocapacitive charge storage are contributed equally at a scan rate of 25 mV s −1 . The ex -situ X-ray powder diffraction and X-ray photoelectron spectroscopy confirmed the pseudocapacitive charge storage rather than capacitive. Moreover, the assembled hybrid supercapacitor (ZCO@CC||AC@CC) provides excellent specific energy of 79.48 Wh kg −1 at a specific power of 894.24 W kg −1 . Further, the ZCO@CC||AC@CC shows superior flexible performance while bending at various angles and demonstrate a negligible change in capacitance by repeating 1000 GCD cycles at each bent state. Therefore, the achieved fascinating pseudocapacitive charge storage properties ensure that the ZCO@CC electrode is a potential material for high-performance hybrid supercapacitors.